Tears of Joy as an Emotional Expression of the Meaning of Life - Paoli, Bernardo; Giubilei, Rachele; De Gregorio, Eugenio (Frontiers in Psychology, 2022)
This article describes a research project in which a qualitative research was carried out consisting of 24 semi-structured interviews and a subsequent data analysis using the MAXQDA software in order to investigate a particular dimorphic emotional expression: tears of joy (TOJ). The working hypothesis is that TOJ are not only an atypical expression due to a “super joy,” or that they are only an attempt by the organism to self-regulate the excess of joyful emotion through the expression of the opposite emotion (sadness), but that it is an emotional experience in its own right—not entirely overlapping with joy—with a specific adaptive function. Through the interviews, conducted in a cross-cultural context (mainly in India and Japan), we explored the following possibility: what if the adaptive function of crying for joy were to signal, to those experiencing it, the meaning of their life; the most important direction given to their existence? The material collected provided positive support for this interpretation.